Does corruption boost or harm firms' performance in developing and emerging economies? A firm‐level study
In the last decade, a growing number of studies have addressed the ongoing debate about whether corruption sands or greases the wheels of business at the firm level. This study revisits this debate and proposes a comprehensive theoretical framework to test whether corruption harms or boosts firm performance, as well as the extent to which this relationship is mediated by the countries institutional settings, the size and strategic behaviour of the firms, and market competition. Based on a sample of 21,250 firms located in 117 emerging and developing countries, and resorting to instrumental variable (IV) estimations, three main results were found: (a) regardless of the proxy used for corruption and firm performance, the former clearly harms the latter; (b) corruption greases the wheels of business for African firms but it sands the wheels for firms in Latin America, the Caribbean, Eastern Europe, Central Asia, and Southern Asia; and (c) the negative impact of corruption on performance is mitigated for larger and exporting firms. (c) 2020 John Wiley & Sons Ltd